Routing protocol for ad hoc mobile networks using mobility prediction. (13th February 2007) - Creixell, Werner; Sezaki, Kaoru
Over the lasts years there has been a growing interest on Mobile Ad Hoc Networks (MANET). Since the nodes can move freely, mobility became an important characteristic of the MANET. In this work we propose a novel prediction method to forecast the future node position. The method was derived using pedestrian tracked data. Using this method we propose a novel geographical routing protocol that uses the predicted position in the routing decision process. The method prediction performance is contrasted against a real trajectory and the routing protocol performance is tested by computer simulations against others geographical routing protocols.